Exploring the Interactions Between Caffeic Acid and Human Serum Albumin Using Spectroscopic and Molecular Docking Techniques - Ali Jahanban-Esfahlan; Leila Roufegarinejad; Mahnaz Tabibiazar; José M. Lorenzo; Ryszard Amarowicz (Polish Journal of Food and Nutrition Sciences)
Ultraviolet-visible (UV–Vis) and fluorescence spectroscopy along with molecular docking were used to explore the interaction between human serum albumin (HSA) and caffeic acid (CA). CA is one of the major representatives of hydroxycinnamic acids in plants and is commonly present in plant-based foods. The mechanism by which CA quenched HSA fluorescence was determined to be static, and the values obtained for thermodynamic parameters indicated that the CA and HSA interaction was spontaneous. Hydrogen bonds and van der Waals forces were the main driving forces stabilizing the complex. The binding constant was in the order of 10 4 /M and the number of binding sites for CA on HSA was calculated to be close to one. The results of fluorescence and UV–Vis spectroscopy showed that CA induced conformational changes in HSA structure. The distance of CA and the tryptophan residue of HSA, was determined to be ~2 nm by using Forster resonance energy transfer theory. The mode of binding and the binding site of CA on albumin were examined by performing molecular docking calculations. CA interacted with albumin in subdomain IA, and non–covalent interactions stabilized the complex. CA showed a high affinity for albumin, and thus this phenolic compound would be distributed in the body upon interacting with HSA.